2010
DOI: 10.2500/aap.2010.31.3366
|View full text |Cite
|
Sign up to set email alerts
|

Comparable effect of a leukotriene receptor antagonist and long-acting beta2-adrenergic agonist in cough variant asthma

Abstract: Cough variant asthma (CVA) is a common cause of chronic persistent cough, in which allergic airway inflammation may play a role. Although current guidelines recommend bronchodilators and anti-inflammatory drugs for the treatment, comparison of the efficacy of these medications has not been investigated. This study was designed to evaluate the effectiveness of pranlukast, a leukotriene receptor antagonist, and salmeterol, a long-acting beta₂-adrenergic agonist, in the treatment of CVA. The study was a randomize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 0 publications
2
16
0
Order By: Relevance
“…In addition, Kim et al [14] found that higher percentage of sputum eosinophils in CVA patients was associated with the development of classic asthma at follow-up, and Fujimura et al [15] reported that treatment with long-term inhaled corticosteroid prevented the development of classic asthma from CVA and reduced bronchial responsiveness. Recently, Tamaoki et al [16] showed that pranlukast, a leukotriene receptor antagonist, caused improvements in cough symptoms and eosinophilic airway inflammation to a greater extent than did salmeterol in patients with CVA. Taken together, anti-inflammatory therapy seems important not only for reduction of cough symptoms but also for prevention of progression to typical asthma in the future.…”
Section: Discussionmentioning
confidence: 98%
“…In addition, Kim et al [14] found that higher percentage of sputum eosinophils in CVA patients was associated with the development of classic asthma at follow-up, and Fujimura et al [15] reported that treatment with long-term inhaled corticosteroid prevented the development of classic asthma from CVA and reduced bronchial responsiveness. Recently, Tamaoki et al [16] showed that pranlukast, a leukotriene receptor antagonist, caused improvements in cough symptoms and eosinophilic airway inflammation to a greater extent than did salmeterol in patients with CVA. Taken together, anti-inflammatory therapy seems important not only for reduction of cough symptoms but also for prevention of progression to typical asthma in the future.…”
Section: Discussionmentioning
confidence: 98%
“…In a randomized, controlled, parallel-group, multicenter trial of 49 patients with newly diagnosed CVA, the LTRA pranlukast improved cough symptom scores to a greater degree than did the long-acting inhaled b 2 -agonist salmeterol. Furthermore, unlike with salmeterol, a 4-week course of therapy with pranlukast significantly decreased eosinophil counts and eosinophil cationic protein (ECP) contents in peripheral blood and induced sputum (Tamaoki et al, 2010). Three studies have demonstrated the antitussive effect of montelukast (10 mg daily).…”
Section: J Leukotriene Receptor Antagonistsmentioning
confidence: 99%
“…Clinical experience has shown that most patients with CVA will experience improvement in cough after 1 week of b 2 -agonist therapy, although full resolution of cough may require up to 8 weeks of treatment, including an ICS (Irwin et al, 1997). However, the leukotriene receptor antagonists (LTRAs) have been shown to be more effective than b 2 -agonists and ICS asthmatic cough in subjects with asthma (Dicpinigaitis et al, 2002;Tamaoki et al, 2010).…”
Section: E B 2 -Agonistsmentioning
confidence: 99%
“…Clinically, the addition of an elective beta‐2 adrenoceptor agonist has been shown to be more effective than doubling the dose of a steroid inhaler . Although the benefits of beta‐2 adrenoceptor agonists plus steroid inhaler are well established for the treatment of classical asthma, to our knowledge, there are few reports demonstrating the efficacy of these agents in patients with CVA …”
Section: Introductionmentioning
confidence: 99%